1989
DOI: 10.1080/03610738908259757
|View full text |Cite
|
Sign up to set email alerts
|

Auditory memory and age-related differences in two-tone frequency discrimination: Trace decay and interference

Abstract: We investigated age-related differences in the time course of two-tone frequency discrimination. Healthy young and elderly adults with normal hearing acuity in the 500-2000 Hz range performed a two-alternative forced choice frequency discrimination task. The stimuli were short tones separated by either a 250-ms (short), 850-ms (medium), or 3000-ms (long) silent inter-interstimulus interval (ISI). Frequency discrimination thresholds were estimated using an adaptive staircase procedure. Although young listeners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Although peripheral losses can be remediated to some degree through the use of assistive technologies such as hearing aids (or, in extreme cases, cochlear implants), central processing deficits seem to persist in spite of such interventions (Chmiel and Jerger, 1996; Killion, 1997). These central processing deficits – including age-related declines in the synchrony of neural firing (Pichora-Fuller and Schneider, 1992; Frisina and Frisina, 1997; Pichora-Fuller et al, 2007), length of recovery time (Walton et al, 1998), and numbers of neurons in auditory nuclei (Frisina and Walton, 2006) – have been associated with age-related losses in key auditory perceptual abilities, such as sound localization (Abel et al, 2000), pitch discrimination (Raz et al, 1989), duration judgments (Fitzgibbons and Gordon-Salant, 1994; Schneider et al, 1994), mistuned harmonic detection (Alain et al, 2001), and speech-in-noise perception (Pichora-Fuller et al, 1995; Russo and Pichora-Fuller, 2008; Schneider et al, 2010). Of the perceptual deficits, the loss of speech-in-noise perception seems to have the most severe impact on the aging adult’s quality of life (e.g., Pichora-Fuller et al, 1995, 2007; Anderson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although peripheral losses can be remediated to some degree through the use of assistive technologies such as hearing aids (or, in extreme cases, cochlear implants), central processing deficits seem to persist in spite of such interventions (Chmiel and Jerger, 1996; Killion, 1997). These central processing deficits – including age-related declines in the synchrony of neural firing (Pichora-Fuller and Schneider, 1992; Frisina and Frisina, 1997; Pichora-Fuller et al, 2007), length of recovery time (Walton et al, 1998), and numbers of neurons in auditory nuclei (Frisina and Walton, 2006) – have been associated with age-related losses in key auditory perceptual abilities, such as sound localization (Abel et al, 2000), pitch discrimination (Raz et al, 1989), duration judgments (Fitzgibbons and Gordon-Salant, 1994; Schneider et al, 1994), mistuned harmonic detection (Alain et al, 2001), and speech-in-noise perception (Pichora-Fuller et al, 1995; Russo and Pichora-Fuller, 2008; Schneider et al, 2010). Of the perceptual deficits, the loss of speech-in-noise perception seems to have the most severe impact on the aging adult’s quality of life (e.g., Pichora-Fuller et al, 1995, 2007; Anderson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related phenomena compatible with increases in sensory persistence have been found in both auditory (Raz et al, 1989;Robin & Royer, 1989) and visual (Kline & Schieber, 1985;Royer & Gilmore, 1985) domains. A potential neural mechanism of increased stimulus persistence has been proposed by Robin and Royer, who suggested that there is an age-related increase in inhibitory interactions of cells sensitive to onset and offset of the stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…At none of the tested frequencies did the mean thresholds of the elderly exceed 21 dB, and there were no significant hearing differences by sex. All listeners had had 3–6 hr of frequency-discrimination training because they had already taken part in at least one of the earlier studies (Raz, Millman, & Moberg, 1989; Raz & Moberg, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These age-related declines lead to impaired processing of acoustic information, whereby temporal and spectral information are not preserved in the neural representation of sounds (Parbery-Clark, Anderson, Hittner, & Kraus, 2012). Such persistent central processing deficits have been associated with age-related losses in key auditory perceptual abilities, including sound localization (Abel, Giguere, Consoli, & Papsin, 2000); pitch discrimination (Raz, Millman, & Moberg, 1989); melodic discrimination (F. A. Russo et al, 2012); duration (Fitzgibbons & Gordon-Salant, 1994), gap (Schneider, Pichora-Fuller, Kowalchuk, & Lamb, 1994), and mistuned harmonic (Alain, McDonald, Ostroff, & Schneider, 2001) detection; and speech perception in noise (Pichora-Fuller, Schneider, & Daneman, 1995;F.…”
Section: Age-related Declines In Central Processingmentioning
confidence: 99%